2017
DOI: 10.1002/jcsm.12235
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed alternatively spliced genes in skeletal muscle from cancer patients with cachexia

Abstract: BackgroundAlternative splicing (AS) is a post‐transcriptional gene regulatory mechanism that contributes to proteome diversity. Aberrant splicing mechanisms contribute to various cancers and muscle‐related conditions such as Duchenne muscular dystrophy. However, dysregulation of AS in cancer cachexia (CC) remains unexplored. Our objectives were (i) to profile alternatively spliced genes (ASGs) on a genome‐wide scale and (ii) to identify differentially expressed alternatively spliced genes (DASGs) associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 69 publications
(123 reference statements)
0
33
0
Order By: Relevance
“…A number of studies have used RA biopsies in cancer patients to delineate biological features associated with low muscle mass and radiodensity . The primary aim of this study was to gain an appreciation of the variation in muscle radiodensity within the RA.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have used RA biopsies in cancer patients to delineate biological features associated with low muscle mass and radiodensity . The primary aim of this study was to gain an appreciation of the variation in muscle radiodensity within the RA.…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with worse clinical outcomes, quality of life and survival. In genomic studies, cachexia-related body mass index alterations in gastrointestinal cancer patients were found to be linked to the Cytokinesis 1 gene 108 and a transcriptome array study by Narasimhan et al 109 identified specific abnormalities in alternative splicing of genes in patients with cancer cachexia. 103 Among the more recent findings, Iwata et al 107 demonstrated that muscle wasting in cancer cachexia follows a different pathway of muscular damage from the one established in muscle dystrophies.…”
Section: Cachexia In Cancermentioning
confidence: 99%
“…103 Among the more recent findings, Iwata et al 107 demonstrated that muscle wasting in cancer cachexia follows a different pathway of muscular damage from the one established in muscle dystrophies. In genomic studies, cachexia-related body mass index alterations in gastrointestinal cancer patients were found to be linked to the Cytokinesis 1 gene 108 and a transcriptome array study by Narasimhan et al 109 identified specific abnormalities in alternative splicing of genes in patients with cancer cachexia.…”
Section: Cachexia In Cancermentioning
confidence: 99%
“…8,9 One of the strongest emerging fields are detailed clinical series of ageing effects, both detailed physiological evaluations 10,11 and large scale cohort reports. [12][13][14][15][16][17] In the area of translational studies in the mechanisms of cachexia, studies were published on expression of spliced skeletal muscle genes, 18 along with scientific evaluations of skeletal muscle physiology, 19,20 growth, wasting, 21-23 preservation, 24,25 and regeneration. 26 Basic science approaches were also used to study the growing interest in the cardiac and cardio-metabolic effects of cancerrelated cachexia and of modern cancer therapies.…”
Section: By Disciplinementioning
confidence: 99%